2022
DOI: 10.1080/21505594.2022.2047506
|View full text |Cite
|
Sign up to set email alerts
|

Association of follicular helper T and follicular regulatory T cells with severity and hyperglycemia in hospitalized COVID-19 patients

Abstract: We aimed to determine the levels of follicular helper T (Tfh) and follicular regulatory T (Tfr) cells in COVID-19 patients and determine whether their levels correlated with disease severity and presence of hyperglycemia. This study was carried out in 34 hospitalized COVID-19 patients and 20 healthy controls. Levels of total circulating Tfh, inducible T-cell costimulator (ICOS)+ activated Tfh, and Tfr cells were assessed in all participants by flow cytometry. Total CD4+CXCR5+ Tfh cells and ICOS+Foxp3-activated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Announced by the World Health Organization in January 2020 as a global health emergency and in March 2020 as a pandemic, coronavirus disease 2019 (COVID-19) is a severe respiratory illness. 1 , 2 COVID-19 is highly infective, presenting with a range of symptoms; however, up to 80% of symptomatic COVID-19 infections feature only flu-like symptoms with no complications; 3 advanced complications such as renal or circulatory failure have been reported with severe cases or with other comorbidities or risk factors including old age, hypertension, cardiovascular diseases, or diabetes, especially type 1 diabetes mellitus (T1DM). 4 …”
Section: Introductionmentioning
confidence: 99%
“…Announced by the World Health Organization in January 2020 as a global health emergency and in March 2020 as a pandemic, coronavirus disease 2019 (COVID-19) is a severe respiratory illness. 1 , 2 COVID-19 is highly infective, presenting with a range of symptoms; however, up to 80% of symptomatic COVID-19 infections feature only flu-like symptoms with no complications; 3 advanced complications such as renal or circulatory failure have been reported with severe cases or with other comorbidities or risk factors including old age, hypertension, cardiovascular diseases, or diabetes, especially type 1 diabetes mellitus (T1DM). 4 …”
Section: Introductionmentioning
confidence: 99%
“…Thus, up-regulation of FOXP3 may be a natural response to develop T regulatory lymphocyte to regulate the pro-inflammatory responses, including IL-17A, IL-8, and CCL20. Previous studies validated the theory and showed that the T regulatory subset develops in hospitalized SARS-CoV-2 infected patients ( Zahran et al, 2022 , Morrell et al, 2022 ).…”
Section: Discussionmentioning
confidence: 59%
“…Adaptive immunity, especially T helper responses, plays important roles against severe acute respiratory syndrome coronavirus 2 (SARS‑CoV‑2) ( Zahran, et al, 2022 ). Excess immune responses to the virus can be associated with severe inflammation and severe morbidity and mortality of the SARS-CoV-2 infected patients ( Chan and Jia, 2011 , Kim et al, 2017 , Yoo et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Tfr cells, a specialized subset of regulatory T (Treg) cells, which not only express numerous Treg-related factors, such as CD25 and FOXP3, but also control excessive germinal centre response [34,35]. Recently, clinical studies have shown that the dysregulated Tfh and Tfr cells as well as an abnormal Tfh/Tfr ratio in primary Sjögren's syndrome, COVID-19 and colitis [36][37][38]. In published data, HIF-1α deficiency remarkedly decreased the percentage of Tfh cells and HIF-1α-dependent glycolysis was required for Tfh cell differentiation [39].…”
Section: Discussionmentioning
confidence: 99%